ELAN VITAL ORANG BANJAR DI PERANTAUAN (Studi Kasus Migrasi dan Adaptasi Orang Banjar di Kabupaten Indragiri Hilir Provinsi Riau) - Putra, Edi Susrianto Indra (Indonesia University of Education, 2011)
This research is aim at studying the power struggle of Banjarese People in Indragiri Hilir Regency in which the focus of study is about the Banjarese People’s migration and adaptation and it’s implication to the social studies subject. The object of this research is to explore the causes of Banjarese People’s migration such as; the motivating factors from the place of origin and the attractions from the place of destination. In addition, this research also describes the adaptation strategy, culture, and the role of Banjarese people’s social capital which forms their power struggle in Shoreline. Further, the procedure of this research is qualitative research in the form of case study. The results of this research are; (1) the migration of Banjarese People is done because of the economy crisis and policy pressure at that time; (2) Indragiri Hilir is chosen as the migration place because it has the same geographic land with their place, thus it is easy for them to work there; (3) the adaptation and the social interaction of Banjarese People hold important role in managing and cooperating with other ethnics in Indragiri Hilir; (4) the social capital, especially the social networking holds important role in maintaining the banjarese identity ethnic in Shoreline.Key words: Migration, Adaptation, Social Capital, Banjarese People’s.